Distribution Characteristics of Nutrients and Eutrophication Assessment in Yueqing Bay - YAO Kaixue; YIN Rui; WANG Yang; CHEN Feng; LI Zhenhua (Haiyang Kaifa yu guanli)
Based on the Marine environment monitoring data of Yueqing Bay in spring, summer, autumn and winter from 2018 to 2019, the spatial and temporal distribution characteristics of nutrient salts (dissolved inorganic nitrogen, DIN) and active phosphate (DIP) in the sea were analyzed, and the pollution degree, eutrophication degree and nutrient structure of the sea area were evaluated by single factor index method, eutrophication index method and potential eutrophication model. The results showed that there were seasonal differences in nutrient concentration in Yueqing Bay, with the average DIN concentration in autumn>summer>spring>winter, and the average DIP concentration in autumn > winter = spring > summer. In terms of spatial distribution, DIN concentration showed a gradual upward trend from the mouth of the bay to the top of the bay, while DIP concentration showed different seasonal distribution trends. A few key aspects that affect the DIN distribution pattern include land source input, seawater cultivation, and engineering construction. The primary factors affecting the distribution pattern of DIP are sediment release, seawater culture, and power plant temperature drainage. The results of the single factor index method showed that the nutrient concentrations of most of the surveyed stations in the four seasons of Yueqing Bay did not meet the second and fourth types of seawater quality standards, and were mainly concentrated in the top and middle of the bay. The results of eutrophication index method showed that the sea area of Yueqing Bay was in a state of eutrophication to varying degrees throughout the year, and it was the most serious in autumn. The analysis of potential eutrophication patterns showed that the N/P ratio of most of the survey stations in this area was generally greater than that of the Redfield ratio (16), and the water were mainly in a phosphorus-restricted state in spring and summer, and unrestricted in autumn and winter.